Investigation of the electronic and optical properties of bulk and monolayer AlxGa(1−x)N structure using density functional theory - Tolasa Tamasgen Hirpha; Gamachis Sakata Gurmesa; Belayneh Mesfin Ali; Genene Shiferaw Aga (Scientific African, 2025)
We investigated the electronic and optical properties of pristine and aluminum doped bulk (3D) and monolayer (2D) GaN (AlxGa(1−x)N) structures. The analysis was carried out using first-principle-based density functional theory with Perdew–Burke–Ernzerhof (PBE), Heyd–Scuseria–Ernzerhof (HSE) hybrid functional, and random phase approximation (RPA). The electronic properties investigations revealed that compared with the PBE values, the HSE calculations of both Al-doped 2D and 3D GaN shows an increase in the band gaps with an increase in the doping concentrations. Moreover, by tuning the concentration of the Al dopant, a p-type GaN can be made to switch to an n-layer both for the bulk and monolayer structures. In the optical properties study, it is found that as the concentration of Al dopants in GaN is increased, the peaks of the real and imaginary parts of the dielectric function of both bulk and monolayer structures are increased for parallel polarizations with the peaks positions steadily shifting towards high photon energy regions. Furthermore, the existence of a local field effect is found to affect the optical characteristics of both Al-doped 3D and 2D GaN structures. The results obtained for the bulk and monolayer AlxGa(1−x)N systems may have potential applications in the optoelectronics and renewable energy sectors.